2015
DOI: 10.1177/0194599815583641
|View full text |Cite
|
Sign up to set email alerts
|

Laryngectomy Complications Are Associated with Perioperative Antibiotic Choice

Abstract: There is substantial variability in perioperative antibiotic strategies for laryngectomy. Clindamycin was associated with much higher odds of short-term complications as compared to other common regimens. Based on these data, clinical trials should be planned to firmly establish the most effective and cost-effective antibiotic management for laryngectomy and determine potential alternatives to clindamycin for penicillin-allergic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 24 publications
5
59
1
Order By: Relevance
“…Previous studies have similarly suggested an increased risk of recipient surgical site infections with prophylactic clindamycin compared to ampicillin‐sulbactam in clean‐contaminated head and neck cases, although this association was not demonstrated in all studies . Surgical site infections in head and neck clean‐contaminated cases are often polymicrobial and can include gram‐negative aerobic bacteria (eg, Escherichia coli , Klebsiella pneumoniae , or Pseudomonas aeruginosa ) for which clindamycin does not offer coverage .…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have similarly suggested an increased risk of recipient surgical site infections with prophylactic clindamycin compared to ampicillin‐sulbactam in clean‐contaminated head and neck cases, although this association was not demonstrated in all studies . Surgical site infections in head and neck clean‐contaminated cases are often polymicrobial and can include gram‐negative aerobic bacteria (eg, Escherichia coli , Klebsiella pneumoniae , or Pseudomonas aeruginosa ) for which clindamycin does not offer coverage .…”
Section: Discussionmentioning
confidence: 90%
“…Both organisms are listed as CDC major health threats and have the capability to colonize the skin, respiratory tract, and prosthetic material used for surgical revision or infusion of IV chemotherapy agents (eg, tracheostomy or indwelling central venous catheters) . Although the incidence of these organisms in SSI is questionable or underreported, the perceived risk and detrimental effects these organisms have on patient outcomes contribute to antibiotic misuse by clinicians …”
Section: Statementsmentioning
confidence: 99%
“…However, antibiotic overuse has become increasingly recognized as a major driving force in the development of global antimicrobial resistance . Moreover, overuse of antibiotics leads to increased healthcare costs and can result in negative consequences to an individual patient including Clostridium difficile infection, renal toxicity, allergic reactions, and rarely, anaphylaxis …”
Section: Introductionmentioning
confidence: 99%